Ethical leadership and nurses’ job performance: the mediating role of self-compassion - Liu, Xingxing; He, Fang; Tian, Tian; Guo, Fangli; Zhang, Jun; Zhong, Yuexia (Frontiers in Public Health, 2025)
BackgroundEthical leadership is crucial in nursing management, and self-compassion is increasingly recognized as a significant factor influencing nurses’ job performance. Although the link between ethical leadership and nurse job performance has been established, the specific mechanisms that underlie this relationship remain unclear. Additionally, there is a paucity of research examining the potential role of self-compassion in this context. This study aims to investigate the relationship between self-compassion, ethical leadership, and nurses’ job performance while also validating the mediating role of self-compassion.MethodsThis study employed a convenience sampling method to conduct a cross-sectional online survey involving 968 nurses from four tertiary-level hospitals in Xi’an, China, conducted between April and May 2024. Participants completed self-report questionnaires that included the Ethical Leadership Scale, Self-Compassion Scale, and Job Performance Scale. Data analysis was performed using descriptive statistics, the Mann–Whitney U test, the Kruskal-Wallis H rank sum test, Spearman correlation analysis, and the PROCESS tool within SPSS.ResultsThe analysis revealed a significant positive correlation between ethical leadership and self-compassion (r = 0.631, p < 0.01), as well as between ethical leadership and job performance (r = 0.688, p < 0.01). Additionally, a positive correlation was found between self-compassion and job performance (r = 0.564, p < 0.01). Mediation analysis indicated that self-compassion partially mediated the relationship between ethical leadership and job performance. The overall impact of ethical leadership on job performance (β = 0.680) comprised a direct effect (β = 0.499) and an indirect effect mediated by self-compassion (β = 0.181). The mediating effect accounted for 26.62% of the total effect.ConclusionThe results of this study indicate that ethical leadership not only directly predicts nurses’ job performance but also indirectly influences it by enhancing their levels of self-compassion. Consequently, nursing managers should prioritize the cultivation and reinforcement of ethical leadership styles while fostering a supportive environment that promotes effective self-compassion practices. Implementing these strategies is essential for improving nurses’ job performance and well-being, ultimately contributing to a higher quality of care and greater stability within the nursing team.